The Role of the Military in Government Bureaucracy: A Juridical Comparative Review of Indonesia and Pakistan - Albab, Biantara; Sulaiman, King Faisal (Universitas Muhammadiyah Yogyakarta, 2026)
This study compares military involvement in the civil bureaucracy in Indonesia and Pakistan. The background of the problem lies in the military's persistent role in government despite reforms aimed at strengthening civilian supremacy. The objective is to analyze the legal framework and authority of military participation in the bureaucracy in both countries. The method used is comparative legal research, focusing on the constitution, legislation, and policies related to civil-military relations. The results reveal that the military's influence in the bureaucracy remains strong despite legal reforms. The difference is that post-reform Indonesia limits the assignment of active-duty TNI personnel to specific civilian positions in the defense and security sectors, subject to the approval of the House of Representatives. In comparison, Pakistan offers a broader scope, extending to cross-sectoral bureaucracy, economic development, and the jurisdiction of military courts over civilians with constitutional protection. In conclusion, both countries provide legal legitimacy for the military's role beyond defense functions, either through constitutional provisions or legislation that explicitly or implicitly open the door to military involvement in non-military sectors. Both Indonesia and Pakistan have legalized military involvement in the civilian sphere, expanding its functions from defense to administrative and development roles.